2009
DOI: 10.1080/17470910802188370
|View full text |Cite
|
Sign up to set email alerts
|

Towards clinical trials of lie detection with fMRI

Abstract: Recent reports of successful fMRI-based discrimination between lie and truth in single subjects raised the interest of prospective users and a public concern about the potential scope of this technology. The increased scrutiny highlighted the lack of controlled "real life", i.e. prospective clinical trials of this technology that conform to the common standards of medical device development. The ethics of conducting such trials given the paucity of data on fMRI-based lie detection has also been questioned. To … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
9
0

Year Published

2010
2010
2014
2014

Publication Types

Select...
4
3
2

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(9 citation statements)
references
References 28 publications
0
9
0
Order By: Relevance
“…Activity in the middle frontal (BA 45) and the inferior parietal (BA 29 & 39) regions was also observed. Activity in these regions has been widely reported in imaging studies on deception by ourselves and others [4], [5], [62]. Prior research has shown that the precuneus is involved in the recollection of past events and, in particular, the retrieval of rich episodic contextual associations [63].…”
Section: Discussionmentioning
confidence: 90%
“…Activity in the middle frontal (BA 45) and the inferior parietal (BA 29 & 39) regions was also observed. Activity in these regions has been widely reported in imaging studies on deception by ourselves and others [4], [5], [62]. Prior research has shown that the precuneus is involved in the recollection of past events and, in particular, the retrieval of rich episodic contextual associations [63].…”
Section: Discussionmentioning
confidence: 90%
“…This would permit meaningful calculations of the error rates, including within-subject accuracy and predictive values. Despite the ethical challenges such trials may pose, forensic functional imaging studies are not inconceivable in both normal and pathological populations (Fullam, McKie, & Dolan, 2009; Hakun et al, 2009; Kozel & Trivedi, 2008; Yang et al, 2007). Another way of estimating new technology’s efficacy is a “head-to-head” comparison between fMRI and the polygraph.…”
Section: The Policy Analysismentioning
confidence: 99%
“…Debate surrounding the accuracy and utility of these techniques has been fierce, but several studies have provided promising evidence for the identification of deceptive patterns of brain activity using fMRI (e.g. Hakun et al, 2009; Monteleone et al, 2009), although countermeasures can be developed which may render the technique useless in practice (Ganis et al, 2011). …”
Section: Introductionmentioning
confidence: 99%